De Sitter en Einstein. ‘Het lijkt mij dat Einstein hier een vergissing begaan heeft’ - Guichelaar, Jan (Studium, 2016)
De Sitter and EinsteinWillem de Sitter’s interest in gravity was based on his work on celestial mechanics, in particular on the four big moons of Jupiter. His work on cosmology was based on the general theory of relativity of Albert Einstein. De Sitter published in 1917, on request of Arthur Eddington to inform the English astronomers, a series of four articles in The Observatory and the Monthly Notices of the Royal Astronomical Society. Einstein developed his own cosmological models, containing mass. De Sitter found a different solution and described a universe without mass. Einstein could not accept De Sitter’s model and they ‘fought out’ two controversies in their correspondence. In theend Einstein had to confess De Sitter was mainly right in his criticisms. In 1932 Einstein and De Sitter published an article on a new model, the so-called Einstein-De Sitter Model of the universe. So, De Sitter was able to do fundamental work in classical celestial mechanics as well as in the new cosmological theories.